ChemInform Abstract: An Aluminum Porphyrin Complex with High Activity and Selectivity for Cyclic Carbonate Synthesis. Issue 38 (3rd September 2015) - Qin, Yusheng; Guo, Hongchen; Sheng, Xingfeng; Wang, Xianhong; Wang, Fosong
Abstract from epoxides and CO2